2013
DOI: 10.2203/dose-response.13-030.doss
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Radiation Adaptive Protection to Control Neurodegenerative Diseases

Abstract: ᮀ Concerns have been expressed recently regarding the observed increased DNA damage from activities such as thinking and exercise. Such concerns have arisen from an incomplete accounting of the full effects of the increased oxidative damage. When the effects of the induced adaptive protective responses such as increased antioxidants and DNA repair enzymes are taken into consideration, there would be less endogenous DNA damage during the subsequent period of enhanced defenses, resulting in improved health from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 60 publications
(76 reference statements)
0
25
0
Order By: Relevance
“…Also, many publications in recent years have demonstrated the disease-preventive effect of LDR for cancer and noncancer diseases. 2,4,21 In conclusion, since the opposing arguments presented by Dr. Little are explainable as discussed above, considering the arguments and evidence presented in my Opening Statement, we can indeed conclude confidently that LDR is beneficial, not harmful.…”
Section: Rebuttal: Mohan Doss Phdmentioning
confidence: 67%
“…Also, many publications in recent years have demonstrated the disease-preventive effect of LDR for cancer and noncancer diseases. 2,4,21 In conclusion, since the opposing arguments presented by Dr. Little are explainable as discussed above, considering the arguments and evidence presented in my Opening Statement, we can indeed conclude confidently that LDR is beneficial, not harmful.…”
Section: Rebuttal: Mohan Doss Phdmentioning
confidence: 67%
“…In the literature, many studies have shown that the high doses of ionizing radiation are harmful for health, and the linear‐no‐threshold model implies that there is a linear relationship between dose and effect. However, more evidence suggests that low ionizing radiation dose below a certain threshold is beneficial for the maintenance of health and disease treatment [31–33]. For instance, Liu [34] reported that LDI simulates most immunologic parameters after whole‐body irradiation by doses within 100 cGy.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the inference that low dose radiation exhibits beneficial effects (hormetic effects), while high dose radiation exhibits toxic effects. The results also showed that previous exposure to low doses (≤10 cGy) of radiation reduces subsequent response (adaptive protection) (Azzam et al 1994;Feinendegen 2005;Day et al 2007;Rithidech and Scott 2008;Rithidech 2012a;Doss 2014) and stimulates immunity (Liu 2007;Yu et al 2013). Currently, the exact molecular mechanisms associated with radiationinduced adaptive protection remain unclear, although several signaling pathways have been proposed (Tang and Loke 2015).…”
Section: Introductionmentioning
confidence: 94%